The Potential of Biogas Slurry and Palm Oil Mill Effluent Slurry as Slow-Release Fertilizer Pellet Through Densification - Widyowanti, Reni Astuti; Ginting, Candra; Renjani, Rengga Arnalis (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Organic fertilizer can yield higher production compared to regular fertilizer if properly applied. Thus, it can be a solution to improve nutrient content of soil. The biggest source of bio slurry in plantation is from Palm Oil Mill Effluent (POME) and cow dung biogas. This research aimed to analyze the residue’s potential from the result of biogas processing and bio slurry from POME as slow-release fertilizer pellet. Bio slurry was processed into pellet through densification process using pellet mill. The research was arranged in a Randomized Block Design method with five slurry compositions as treatments, including 70:30, 60:40, 50:50, 40:60, and 30:70 (ratio of biogas slurry and POME slurry), each consisted of three replications. According to the data obtained, fertilizer pellets had characteristics of 25 – 29 mm of length, 5.23 – 5.85 mm of diameter, 0.44 – 0.53 g/cm3 of density, 54.78% - 81.96% of durability, and 7.81% - 8.57% of moisture content. Based on density and durability aspects, 30:70 composition was the higher. Macronutrient content of the five compositions were 1.88% - 2.72%, in which on day 22, N, P, and K release was 0.36 – 1.01%, 73.51 – 97.48%, and 3.19 – 7.85%, respectively. Meanwhile, on day 17, the nutrition solution conductivity of all compositions had already reached 0.80 – 1 mS/cm.